How does young adults’ dietary and health-related quality of life vary by food security and household income? - Kim, Eun-kyung; Kwon, Yong-Seok; Kim, Sena; Lee, Jin-Young; Park, Young Hee (Frontiers in Nutrition, 2024)
The objective of this study was to compare the dietary and health-related quality of life of young adults according to their household income and food security status.To conduct this study, 10,224 young adults aged 19-34 years who participated in the 2008-2018 Korea National Health and Nutrition Examination Survey (KNHANES) were selected. Subjects were categorized into four groups based on household income and food security: 'Food secure & high income', 'Food insecure & high income', 'Food secure & low income', and 'Food insecure & low income'. General characteristics, daily diet, and dietary quality were compared among the four groups.The proportion of participants consuming a daily diet below the estimated average requirements for protein, vitamins A, B1, B2, niacin, vitamin C, calcium, phosphorus, and iron increased in the 'Food insecure & low income' group. Among the most commonly consumed foods, instant noodles and Sprite ranked relatively high in the 'Food insecure & low income' group, while apples and beef ranked relatively high in the 'Food secure & high income' group. The food insecure and low income group exhibited significantly increased rates of mobility problems [OR=1.55(95% CI=1.05-2.29)] and anxiety/depression [OR=1.33(95% CI=1.07-1.64)] in comparison to the food secure and high income group.Food insecurity was positively associated with poor diet quality and was associated with health-related quality of life, mobility, and anxiety/depression, especially among young adults.